2010
DOI: 10.1002/elan.200900438
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Electron Transfer and Oxygen Reduction Reaction at Nanostructured Iron(II) Phthalocyanine and Its MWCNTs Nanocomposites

Abstract: Electron transfer and oxygen reduction dynamics at nanostructured iron(II) phthalocyanine/multi-walled carbon nanotubes composite supported on an edge plane pyrolytic graphite electrode (EPPGE-MWCNT-nanoFePc) platform have been reported. All the electrodes showed the category 3 diffusional behaviour according to the Davies -Compton theoretical framework. Both MWCNTs and MWCNT-nanoFePc showed huge current responses compared to the other electrodes, suggesting the redox processes of trapped redox species within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…Next, the type of the diffusion process that could be occurring at the Pt/NiNP electrode was interrogated by using the ''diffusion domain approximation'' theory developed by Davies and Compton [30,31] which can also be applied to a three-dimensional electrochemically heterogeneous electrode [32]. It can be seen in Fig.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…Next, the type of the diffusion process that could be occurring at the Pt/NiNP electrode was interrogated by using the ''diffusion domain approximation'' theory developed by Davies and Compton [30,31] which can also be applied to a three-dimensional electrochemically heterogeneous electrode [32]. It can be seen in Fig.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…Their intriguing properties have attracted much attention after the discovery that Co-Pc might replace platinum as an electrocatalyst in the ORR [6,7]; in extensive follow-up studies [8][9][10][11][12][13][14][15][16][17][18][19][20] it was reported that a pyrolyzed transition-metal Pc can be even more effective. In addition, pyrolyzed phthalocyanines have been used more recently as raw materials in the production of carbon nanotubes [21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16]. Despite the popularity of ruthenium-based electrocatalysts for ORR, as elegantly reviewed recently by Lee and Popov [1], the use of ruthenium phthalocyanine (RuPc) complexes in ORR is virtually unknown.…”
mentioning
confidence: 99%